Comparação da dor pós-operatória em cães versus gatos após orquiectomia versus ovariohisterectomia - Quarterone, Carolina [UNESP] (2014)
Veterinarians attribute a higher pain scores and give more analgesics to dogs compared to cats. Both female dogs and cats receive more analgesia than males for the same surgical procedures. This study aimed to compare the expression of pain after orquiectomy and ovariohisterectomy of the same species and between the canine and feline species undergoing contraceptive surgery. Cats (24) and dogs (24) were enrolled in the study, with the same number of males and females. The animals were admitted 24 hours prior to the study for adaptation to the hospital environment and the observer. Meloxicam (0.1 mg/kg P.O.) was administered two hours before the surgical procedure. Pain scales were applied before (basal) and 1, 2, 4, 8 and 24 hours after surgery (M1, M2, M4, M8 and M24 respectively). Glasgow Composite Measure Pain Scale (GCMS) and Melbourne pain scale (MPS) were used in dogs, and UNESP-Botucatu Multidimensional Composite Pain Scale (UBMCP) in cats. When the score was above 33% for GCMS or 27% for MPS, analgesic rescue was given (morphine, 0.5 mg/kg for dogs and 0.3 mg/kg for cats). In both species the visual analogue pain scale (VAS) and sedation were recorded. Mann-Whitney was used to compare data between male and female (P < 0.05). Kruskall-Wallis was used to compare differences among groups, followed by Dunn test (P < 0.05). Friedman test compared differences along time (P < 0.05). When compared to baseline female dogs and cats had greater VAS from 1 to 4 h, male dogs and cats from 1 to 8 h and from 1 to 2 h after surgery, respectively. VAS values were higher in female dogs from 1 to 8 h than in male ones, and in female cats this value were higher at 4 h, compared to male cats. In GCMS, scores were greater compared to baseline for females between 1 and 4 h after surgery and at 1 h compared to males. There was no difference for MPS. For UBMCP, greater scores were observed in females compared to males between 1 and 2 h and at 2 h ...